NATIONALISM, RELIGION AND GLOBALIZATION - Sastrapratedja, M (Journal of Dharma, 2000)
Nationalism has again become an issue in various current social science studies. Such is not surprising since after the collapse of communism, the USSR and other East European countries nineteen new different countries have been formed, fourteen of which have been the result of the dissolution of the USSR. An those countries state themselves as natiori states. Thus, in reality the concepts of "nation" and "nationalism" are still the determil1ing principle of political organizations. The issue of nationatsrn has also been important in social science studies because of the emergence of group struggles for independence or ethnic autonomy in a nation state; the latter took place among others in Kosovo and triggered ethnic cleansing in the former parts of Yugoslavia. On the other hand, there has been a strong tendency to see the above issues from a perspective wider than of a nation-state, such as in the framework of international reiation theories, the world system theory, as presented by Wallerstein, and in the globalization framework as in Anthony Giddens.